Simulation of Co-Crystal Solubility in the Mono-Solvents at Different Temperatures - Ali Shayanfar; Abolghasem Jouyban (Sustainable Chemical Engineering, 2024)
This communication reports correlative models for the simulation of the solubility of co-crystals dissolved in mono-solvents at various temperatures. The trained models provided reasonably accurate results for three investigated co-crystals (as model co-crystals) by using Abraham, Hansen and Catalan parameters of the mono-solvents as input values.